Mariages et homosexualités dans le monde: l'arrangement des normes familiales - Descoutures, Virginie (Collection Mutations, 2008)
Revendiquer le droit de se marier et d'avoir des enfants pour des couples homosexuels serait-il une avant-garde, une émancipation par rapport à la norme, ou au contraire le signe d'un grand conformisme? Le fait est que rendre légaux le mariage et la parentalité homosexuels conduit à de nouvelles définitions de la famille en général. Des chercheurs présentent ici le résultat de leurs enquêtes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; angleterre; approches et analyses; belgique; corps; cours; discipline; discours dominant; espagne; europe; france; hétérosexisme; identités LGBTQIA2+; mariage; maternité; parentalité; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Émergence et activités de l’organisation internationale des intersexué·e·s - Guillot, Vincent (Nouvelles Questions Feministes, 2008)
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; europe; histoire et politique; hétérosexisme; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Mind the Gaps: Intersex and (Re-productive) Spaces in Disability Studies and Bioethics - Holmes, M. Morgan (Journal of Bioethical Inquiry, 2008)
With a few notable exceptions disability studies has not taken account of intersexuality, and it is principally through the lenses of feminist and queer-theory oriented ethical discussions but not through ‘straight’ bioethics that modes valuing intersex difference have been proposed. Meanwhile, the medical presupposition that intersex characteristics are inherently disabling to social viability remains the taken-for-granted truth from which clinical practice proceeds. In this paper I argue against bioethical perspectives that justify extensive and invasive pre- and post-natal medical interference to eradicate intersex. I argue instead that to constitute the necessary conditions for the recognition of the intersexed child as a person, a life valid in its own right, clinicians must refrain from aggressive interference. Clinical specialists presuppose that intersexed children will be socially disabled and unrecognizable as persons; frustrated by the general failure of traditional interventions to assign a sex, clinicians are now pursuing prenatal technologies, including selective termination, to erase intersex.
Keywords: LGBTQIA2+; approches et analyses; biologie; bioéthique; corps; cours; discipline; identités LGBTQIA2+; intersexuation; lit4700; médecine; premier cycle; queer; sciences; soc2014; thématiques; éthique

Démédicaliser les corps, politiser les identités : convergences des luttes féministes et intersexes - Kraus, Cynthia; Perrin, Céline; Rey, Séverine; Gosselin, Lucie; Guillot, Vincent (Nouvelles Questions Féministes, 2008)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; belgique; capacitisme; corps; cours; discipline; discours dominant; europe; france; féminisme interdisciplinaire; féminisme matérialiste; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; luxembourg; marginalisation; militance; médecine; philosophie; premier cycle; psychiatrie; périodes historiques; queer; régions géographiques; santé; sciences; sciences humaines; soc2014; soc2051; sociologie; systèmes d'oppressions; thématiques; transféminisme; violences; violences médicales